Reflections on the intriguing occurrence of some recently isolated natural products as racemates and scalemic mixtures. Issue 12 (11th October 2021) - Zask, Arie; Ellestad, George A.
Abstract: This review continues our interest in the intriguing reports of a variety of new racemic natural products (at least 11 in the past 4 years). These include the polyphenolic racemate galewone, the polycyclic prenylated acylphloroglucinol garcinielliptone; variecolortide, a combination of an anthraquinone and a isochinulin‐type alkaloid; the isoindoline alkaloid irpexine, the new hybrid phenylproanoid asarone; colletopyandione an indolydenepyradione; the enantiomerically enriched (scalemic) neolignans, gardenifolins; and meroterpenoid pabmaragramin in addition to some marine lipids. We also present a recent biomimetic synthesis of the polyketide preuisolactone A; synthesis of the polyketide spiromamakone A, which also corrected the proposed structure of another metabolite as identical to spiromamakone A; and the melicolones A and B. The continuing reports of natural racemates provoke speculation as to their role in the producing organism. Abstract : The racemic melipatulinone metabolites, reported by Vu et al. from Melicope patulinervia in the Rutaceae plant family, are recently reported 2020 synergistic examples. In this case, the racemate was 2 to 5 times more active than the individual enantiomers against pancreatic lipase.